ExoPranayama: a biofeedback-driven actuated environment for supporting yoga breathing practices - Moran, Stuart; Jäger, Nils; Schnädelbach, Holger; Glover, Kevin (Springer, 2016)
Both breathing and internal self-awareness are an integral part of any yoga practice. We describe and discuss the development of ExoPranayama, an actuated environment that physically manifests users’ breathing in yoga. Through a series of trials with yoga practitioners and expert teachers, we explore its role in the practice of yoga. Our interview results reveal that biofeedback through the environment supported teaching and improved self-awareness, but it impacted group cohesion. Two practical uses of the technology emerged for supporting breath control in yoga: (1) biofeedback can provide new information about users’ current internal states; (2) machine-driven feedback provides users with a future state or goal, and leads to improved cohesiveness.